2015
DOI: 10.1080/15524256.2015.1115801
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in Adult Bereavement: Preliminary Findings From Five Hospice Bereavement Focus Groups

Abstract: Grief is an experience of both common and unique responses (Hooyman & Kramer, 2006). Grief affects people in various ways including emotionally, cognitively, socially, physically, and spiritually (Corr, 2007; Doka, 2014). Little has been published on the cognitive domain of loss affecting attention, and concentration of bereaved adults. This qualitative study explored these effects among adults in one hospice bereavement program in Central Texas. Five focus groups included facilitated bereavement topical conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…Although Harris et al (2015) identified sleep as potentially related to a decline in cognitive function during bereavement, our study did not support these findings. One explanation may be the difference in study design.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Although Harris et al (2015) identified sleep as potentially related to a decline in cognitive function during bereavement, our study did not support these findings. One explanation may be the difference in study design.…”
Section: Discussioncontrasting
confidence: 97%
“…Furthermore, using findings from a qualitative study, our study also quantitatively examined sleep in relation to cognitive function in bereavement. 15 Finally, self-efficacy to manage emotions, a novel concept, was explored in relation to The psychological factors, anxiety and depression, have been demonstrated to be a separate and distinct experience from grief. 9 Thus, we used both variables in our model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, while a number of publications mentioned treating safely [2,3,20] not one publication mentioned the potential for bereaved individuals to have increased vulnerability. The importance of this is paramount as vulnerable individuals may not be able to communicate their needs as efficiently as non-bereaved individuals making miscommunication more likely to occur [29,30]. In addition, bereaved individuals may be more vulnerable to trauma (either emotionally, verbally or physically) and therapists need to be aware of their actions to limit any possible trauma [31].…”
Section: Discussionmentioning
confidence: 99%